Climate change and migration security and borders in a warming world - White, Gregory, 1960- (New York : Oxford University Press, 2011)
Focusing on climate-induced migration from Africa to Europe White shows how global warming's impact on international relations has been significant, enhancing the security regimes in not only the advanced economies of the North Atlantic, but in the states that serve as transit points between the most advanced and desperate nations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Emigration and immigration -- Social aspects; Emigration and immigration -- Environmental aspects; Climatic changes -- Social aspects; Global environmental change -- Social aspects; Global warming -- Social aspects